Taking modern legislation seriously: Agency rights as a special challenge - Guibentif, P. (Conceptions and misconceptions of legislation, 2019)
The functions of legislation are diverse and its actual impact on its addressees may vary considerably, in relation to different types of legal mechanisms. So legisprudence has to develop scholarship specialized in those different legal mechanisms. One mechanism deserving particular attention are the legal rights, and among them, what could be named agency rights. The purpose of the present paper is to put forward a tentative legisprudential discussion of such rights. After having defined agency rights by locating them in a typology of legal rights, it seeks to reconstruct their societal functions, analysing them as taking part in a broader set of mechanisms, which developed over the last centuries, and which are supposed to enable individuals to act as autonomous and productive members of the societies to which they belong. It pays particular attention to the role of specialists, and among them of jurists, in the functioning of these mechanisms, both as holders of agency rights, and as participating in the empowering of those who are expected to exercise their agency rights. It concludes arguing that legisprudence, by participating in the improvement of legislation guaranteeing these rights, might be playing a crucial role in the improvement of democratic institutions.